(untitled) (Revista Electrónica REDINE, 2024)
This article proposes a reflection on higher education as a field of knowledge that addresses the relationship between pedagogical practices and university social responsibility. From an interpretative perspective, it reviews the challenges facing higher education in relation to pedagogy, didactics and social responsibility, which in turn function as pillars of action for a changing university environment. In order to achieve this reflection, it was necessary to analyze higher education as a field of knowledge with specific characteristics and endowed with normativity that provides consistency. At the same time, it was necessary to study the pedagogical and didactic component in the search for an interpretation of the university phenomenon that allows a continuous discussion on the challenges that imply rethinking the mission of today’s university, from the idea of being an adaptable space in constant harmony with the environment.